A Study of Women’S Diasporic Identity In the Selected Novels of Anita Desai: Exploring the Ambivalent World of Anita Desai's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The world of Anita Desai’s novels is an ambivalent one; it is a worldwhere harmony is aspired but often not achieved; and the desire to live lifefully with proper zeal and love, clashes, at times violently, with the desireto withdraw and keep inwards. Instinct, emotion, passion appear to be strangersin the world of sordid daily routine. Anita Desai’s fictions are marked by‘existential’ themes. Aspects of ‘existentialism’ are reflected in hercharacters in the form of fragmented individuals, alienated and estranged, bothemotionally and spiritually, from the ‘normal society’.